Potensi Tumbuhan Sumber Pangan Hutan di KPH Produksi Unit VIII Muntai Palas Kabupaten Bangka Selatan - Chairullah; Ervizal AM Zuhud; Edy Nasriadi Sambas (Jurnal Pengelolaan Sumberdaya Alam dan Lingkungan (Journal of Natural Resources and Environmental Management), 2021)
Abstract: Plants as forest food sources have potential comparative advantages as alternative resources. The existence of the Production KPH Unit VIII Muntai Palas as a management unit can improve the quality of forest management in South Bangka Regency, Bangka Belitung Islands Province. The purpose of this research was to take an inventory, analyze the utilization and formulate a conservation village development strategy. This research is explorative with the method of determining four village locations (Kepoh, Pasir Putih, Batu Betumpang, and Bencah) and selecting informants by purposive sampling. The results of the study found 33 families, 54 genera, 73 species with a total of 1858 individuals consisting of 1.071 seedlings, 385 saplings, 173 poles and 226 trees. The highest value of species diversity in the medium category was found in Kepoh village, while the species with the highest value of importance (LUVI) differed in each observation village. Kepoh was owned by Sandoricum koetjape Village (LUVI 11.14), Pasir Putih village was mostly inhabitated by Mangifera odorata (kuweni) with a LUVI value of 9.68, Batu Betumpang Village was mostly covered by Nephelium lappaceum (rambutan) (LUVI 11.20) and Bencah village (LUVI 10.84 ) belongs to Garcinia nigrolineata (kandis). The Strength-Opportunity (SO) strategy was applied in the development of sustainable forest conservation villages with the support of the diversity of forest food sources and regional policies as well as opportunities for the development of tourism forests, health forests, educational forests, natural laboratories and investment in natural resources and the environment to realize a sovereign forest conservation village. independent food. Keywords: AHP-SWOT, food source plantation forest, KPH, LUVI, vegetation analysis